Role of endoplasmic-reticulum-associated protein degradation pathway in the virus infection cycle - Wandtke, Tomasz; Wędrowska, Ewelina; Goede, Arkadiusz; Owczarska, Paulina; Piskorska, Elżbieta; Kopiński, Piotr (Journal of Education, Health and Sport, 2017)
Introduction: The endoplasmic-reticulum-associated protein degradation (ERAD) pathway plays an important role in maintaining intracellular homeostasis and primarily affects proteins that have not achieved correct post-translational conformation. ERAD can be also exploited by viruses, usually in order to avoid detection by the host’s immune system. Depending on the type of virus, the character and manner of protein degradation may be different. Aim of the study: The aim of this paper is to present the ERAD mechanism and its importance for the infection cycle of select viral particles. Gaining knowledge about this process can help to identify potentially effective new antiviral therapies. Short description of state of knowledge: The ERAD mechanism and its utilization by: Poliomaviruses (BK and SV-40), Herpesviruses (Cytomegalovirus), Retroviruses (HIV-I) and Hepadnaviruses (HBV) are discussed in the paper. Summation: The ERAD process in the viral infection cycle is extremely important. The possibility of using ERAD by differnet viruses should be further investigated. It could be also useful to exploit proteasome inhibitors as potential drugs in the fight against viral diseases.